Effects of Standardized Ileal Digestible Lysine on Nursery Pig Growth Performance - C. M. Vier; I. B. De Souza; J. A. De Jong; M. A. Goncalves; A. M. Jones; R. D. Goodband; M. D. Tokach; J. M. DeRouchey; J. C. Woodworth; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2015)
Lysine is the first limiting amino acid in swine diets, thus providing the appropriate level in the diet is critical to growth performance. Therefore, the objective of this study was to determine the standardized ileal digestible (SID) Lys requirement of nursery pigs from 15 to 35 lb. A total of 300 maternal line barrows (200 × 400, DNA, Columbus, NE; initially 14.9 ± 0.5 lb BW) were fed six experimental diets as part of a 21-d trial. Pigs were randomly allotted to pens at weaning based on BW, and were fed a common pelleted diet for 9 d after weaning. Pens were then randomly assigned to dietary treatments (10 pens/treatment with 5 pigs/pen) based on average pig weight. The six dietary treatments had increasing SID Lys (1.05, 1.15, 1.25, 1.35, 1.45, and 1.55%) and were achieved by increasing the inclusion of crystalline AA, allowing soybean meal to stay constant across dietary treatments. Experimental data were analyzed using general linear and non-linear mixed models with heterogeneous residual variances. Competing models included linear (LM), quadratic polynomial (QP), broken-line linear (BLL), and broken-line quadratic (BLQ). For ADG, F/G, and IOFC, the best-fitting model was selected using Bayesian information criterion. Overall, increasing SID Lys improved (linear, P<0.05) ADG and F/G. There was also a tendency for a quadratic response for ADG (P<0.10) with increasing SID Lys. The ADFI increased (quadratic, P<0.05) from 1.05 to 1.25% SID Lys with little improvement thereafter. For ADG, the best-fitting comparable models were BLL and BLQ, in which the maximum mean ADG was estimated at 1.29% (95% CI: 1.23, 1.35%) and 1.47% (95% CI: 1.31,>1.55%) SID Lys, respectively. For F/G, the best-fitting model was the LM where F/G was improved up to at least 1.55% SID Lys. For income over feed cost (IOFC), the best-fitting model was the BLL, in which the maximum mean IOFC was estimated at 1.25% (95% CI: 1.14, 1.36%). In conclusion, the estimated SID Lys required for maximum mean ADG of these maternal line barrows was lower than the estimated mean SID Lys required for maximum mean F/G. This study provides evidence that different response variables can result in different estimates of the requirements; however, at least 1.25% SID Lys was needed to maximize IOFC.
Keywords: growth; lysine; nursery pig